Advanced Interface Design for IIIF. A Digital Tool to Explore Image Collections at Different Scales - Rodighiero, Dario; Romele, Alberto; Higuera Rubio, José; Pedro, Celeste; Azzi, Matteo; Uboldi, Giorgio (Umanistica Digitale, 2023)
This article introduces a proposal for an experimental interface design that uses the International Image Interoperability Framework (IIIF) to facilitate the exploration of image collections through the navigation of relational models created by the scholarly practice of annotation. Within the project From Data To Wisdom, an innovative digital tool was designed by harnessing IIIF resources and leveraging close and distant reading on three levels of detail: micro, meso, and macro. The proposed tool integrates annotation features that enable scholars to analyze individual images and interpret broader connections and patterns across image sets. This article outlines the experimental interface’s theoretical framework, design principles, and significant advantages, highlighting the potential to support interdisciplinary research and advancements in digital art.